The influence of disturbance location and intensity on the deformation and failure of deep roadway surrounding rocks - Zhang, Tao; Xu, Yunyun; Wei, Chao; Su, Haijian; Feng, Yujie; Yu, Liyuan (Frontiers in Materials, 2025)
The surrounding rocks in deep roadways frequently undergo dynamic disturbances caused by adjacent blasting or mining activities. These dynamic disturbances lead to the propagation and coalescence of cracks in the surrounding rock, inducing dynamic disasters in the roadways. However, the mechanisms of rock crack propagation and the roadway failures, induced by dynamic disturbances under different blasting positions and strengths, remain unclear. To investigate the dynamic disturbance of deep roadway surrounding rocks, large-scale physical model tests are carried out on the dynamic instability of surrounding rock under high in situ stress and dynamic disturbance. The dynamic instability failure modes under different disturbance loads and positions are analyzed. The results suggest that under conditions of high ground stress, cracks initiate in stress concentration zones in deep roadways. As disturbance intensities increase, these cracks can further extend, leading to the rapid failure of the surrounding rock. The location of dynamic disturbances influences the failure process of the surrounding rock in deep roadways. Under such stress conditions, stress concentration often occurs at the arch shoulder and arch bottom of the roadway. When the source of dynamic disturbance changes from the side wall to the arch, it is more likely to cause damage within the stress concentration zones in the arch shoulder and arch bottom, which can result in instability and failure of the roadways.